2016
DOI: 10.1371/journal.pone.0154602
|View full text |Cite|
|
Sign up to set email alerts
|

The Holstein Friesian Lethal Haplotype 5 (HH5) Results from a Complete Deletion of TBF1M and Cholesterol Deficiency (CDH) from an ERV-(LTR) Insertion into the Coding Region of APOB

Abstract: BackgroundWith the availability of massive SNP data for several economically important cattle breeds, haplotype tests have been performed to identify unknown recessive disorders. A number of so-called lethal haplotypes, have been uncovered in Holstein Friesian cattle and, for at least seven of these, the causative mutations have been identified in candidate genes. However, several lethal haplotypes still remain elusive. Here we report the molecular genetic causes of lethal haplotype 5 (HH5) and cholesterol def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
56
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 44 publications
4
56
0
1
Order By: Relevance
“…Kipp et al (2015) estimated carrier frequency in German Holstein cattle as around 8.7% (among 3,400 screened). In another study, Schütz et al (2016) found 12,5% carriers among Holstein bull born between 2012 and 2015 in Germany. Results presented in our paper show that causal mutation for CD is already transmitted to Polish Holstein-Friesian cattle and, in our opinion, it is sufficient ground to take practical actions in order to avoid further spreading of cholesterol deficiency defect.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Kipp et al (2015) estimated carrier frequency in German Holstein cattle as around 8.7% (among 3,400 screened). In another study, Schütz et al (2016) found 12,5% carriers among Holstein bull born between 2012 and 2015 in Germany. Results presented in our paper show that causal mutation for CD is already transmitted to Polish Holstein-Friesian cattle and, in our opinion, it is sufficient ground to take practical actions in order to avoid further spreading of cholesterol deficiency defect.…”
Section: Resultsmentioning
confidence: 90%
“…The 1.3kb insertion was confirmed by Schütz et al (2016), who reported that the LTR element was inserted into exon 5 of the APOB gene (at BTA11:77,959kb) and is flanked by 6bp target site duplications typical to insertions mediated by retroviral integrases. APOB is an essential compound of chylomicrons and low-density lipoproteins.…”
Section: Introductionmentioning
confidence: 84%
“…The phenotypic impact of SVs in cattle is well evident from numerous studies. For example, Xu et al 6 showed that a combination of SNPs with SVs could explain additional genetic variance underlying milk production traits, while Charlier et al, 7 Schutz et al, 8 and Kadri et al, 9 showed the lethal effect of large deletions in dairy cattle. Furthermore, a ∼525 KB deletion on chromosome 23 is reported to be associated with stillbirth in Nordic Red Cattle 10 …”
Section: Introductionmentioning
confidence: 99%
“…; Schütz et al . ). This previously unknown fat metabolism disorder was termed cholesterol deficiency (CD; OMIA 001965‐9913).…”
mentioning
confidence: 97%